Getting ON-TRAC, a team-centred design study of a reflexivity aid to support resuscitation teams’ information sharing - Lars Mommers; Dennie Wulterkens; Steven Winkel; Bas van den Bogaard; Walter J. Eppich; Walther N. K. A. van Mook (Advances in Simulation)
Abstract Background Effective information sharing is crucial for emergency care teams to maintain an accurate shared mental model. This study describes the design, simulation-based testing and implementation of a team reflexivity aid to facilitate in-action information sharing during resuscitations. Methods A five-phase team-centred iterative design process was employed. Phase 1 involved a literature review to identify in-action cognitive aids. Phase 2 focused on conceptual design, followed by simulation-based testing and modifications in phase 3. Implementation through simulation-based user training occurred in phase 4 at a large non-university teaching hospital. Phase 5 evaluated the aid among resuscitation team members in the emergency department after one year. Results The phase 1 literature review identified 58 cognitive aids, with only 10 designed as ‘team aid’. Studies using team information screens found increase team and task performance in simulation-based environments, with no evaluations in authentic workplaces. Phase 2 resulted in a three-section team reflexivity aid, iteratively modified in three rounds of simulation-based testing (N = 30 groups) phase 3 resulted in a team reflexivity aid containing five sections: resuscitation times and intervals, patient history, interventions on a longitudinal timeline, differential diagnosis and a quick review section. Phase 4 consisted of reflexivity aid user training with simulation-based education (N = 60 sessions) and the creation of a digital entry form to store data in the patient’s electronic medical record. Evaluation after one year in phase 5, (N = 84) showed perceived improvements in communication (3.82 ± 0.77), documentation (4.25 ± 0.66), cognitive load (3.94 ± 0.68), and team performance (3.80 ± 0.76) on a 5-point Likert scale. Thematic analysis of user feedback identified improvements in both teamwork and taskwork. Teamwork enhancements included better situation awareness, communication and team participation. Taskwork improvements were seen in drug administration and clinical reasoning. Conclusions This study demonstrated the successful development and implementation of a Team Reflexivity Aid for Cardiac arrests using simulation methodology. This task-focused team tool improved perceived team situation awareness, communication, and overall performance. The research highlights the interplay between task- and teamwork in healthcare settings, underscoring the potential for taskwork-oriented tools to benefit team dynamics. These findings warrant further investigation into team-supportive interventions and their impact on resuscitation outcomes.